Triatoma vitticeps subcomplex (Hemiptera, Reduviidae, Triatominae): a new grouping of Chagas disease vectors from South America - Chaboli Alevi, Kaio Cesar [UNESP]; Oliveira, Jader de [UNESP]; Vilela de Azeredo-Oliveira, Maria Tercilia [UNESP]; Rosa, Joao Aristeu da [UNESP] (Biomed Central Ltd, 2017)
Background: Triatomines have been grouped into complexes and subcomplexes based largely on morphological and geographical distribution. Although these groupings are not formally recognised as taxonomic ranks, they are likely monophyletic. However, recent studies have demonstrated that some subcomplexes from South America did not form monophyletic groups, and reorganisations have been suggested. One suggested reorganisation is to exclude Triatoma vitticeps, T. melanocephala, and T. tibiamaculata from the T. brasiliensis subcomplex. However, T. vitticeps and T. melanocephala exhibit several similar characteristics, including morphologic, cytogenetic, and phylogenetic features, a factor which supports the creation of a new subcomplex. Thus, this study aimed to describe the T. vitticeps subcomplex. Results: T. vitticeps and T. melanocephala are sister species and share a phylogenetic relationship, several similar morphological characteristics, the same composition of constitutive heterochromatin (Xs CG-rich and Y AT-rich), the same karyotype (2n = 20A + X1X2X3Y), and the same meiotic behaviour during spermatogenesis. Based on karyosystematics, for example, the T. vitticeps subcomplex may differ from all of the other subcomplexes from South America, as well as from the Rhodniini tribe and the genus Panstrongylus. We argue that the case of agmatoploidy involving the X chromosome was responsible for the karyotype divergence of this subcomplex in relation to the other South America subcomplexes. Conclusions: Based on the phenotypic characteristics (morphology) and genotypes (cytogenetics and molecular features), we propose the creation of the monophyletic T. vitticeps subcomplex, which we believe is distinct from all other subcomplexes from South America.
Keywords: Triatoma vitticeps; Triatoma melanocephala; Triatomini tribe